2023
DOI: 10.3390/life13020256
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Level of Advanced Glycation End Products and Objective Skin Quality Parameters

Abstract: Advanced glycation end products (AGEs) represent an endogenously produced or exogenously derived group of compounds derived from nonenzymatic glycation. Recent experimental studies are suggesting that AGEs could play an important role in the skin’s quality and its aging process. Hence, the aim of this study was to clinically evaluate the AGEs and skin quality parameters across different age groups in the general population. The study included 237 participants. Melanin, erythema, hydration, friction and transep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
3
1
0
Order By: Relevance
“…Therefore, treatment with deglycation enzymes may improve scar quality in terms of elasticity and suppleness. Furthermore, a recent study found a link between pigmentation and erythema on the one hand and AGEs on the other [10]. This is in line with previous research describing the AGE-induced promotion of melanogenesis through melanocyte receptor stimulation eventually leading to pigmentation disorders [10,37].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, treatment with deglycation enzymes may improve scar quality in terms of elasticity and suppleness. Furthermore, a recent study found a link between pigmentation and erythema on the one hand and AGEs on the other [10]. This is in line with previous research describing the AGE-induced promotion of melanogenesis through melanocyte receptor stimulation eventually leading to pigmentation disorders [10,37].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, a recent study found a link between pigmentation and erythema on the one hand and AGEs on the other [10]. This is in line with previous research describing the AGE-induced promotion of melanogenesis through melanocyte receptor stimulation eventually leading to pigmentation disorders [10,37]. The effects of FN3K and FAOD on skin color, including erythema and pigmentation factors, in both anti-aging and scar improvement settings, should be the subject of future research.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We observed a significant correlation between age and the accumulation of AGEs in the skin, which may manifest as increased skin yellowness. A previous study has identified significant associations between AGEs and age, melanin level, and erythema as positive predictors 15 . We also observed a remarkable positive correlation between scalp skin yellowness and skin AGEs in bivariate correlation analysis, further emphasizing the intricate relationship between the biological aging process and alterations in scalp biophysical parameters.…”
Section: Discussionsupporting
confidence: 77%